Thallium (III) disrupts the cell cycle and induces oxidative DNA damage in human lymphocytes in vitro - Alejandra López-Lanuza; Lucila Álvarez-Barrera; Hugo López-Muñoz; Rodrigo Aníbal Mateos-Nava; Juan José Rodríguez-Mercado (Current Research in Toxicology)
Thallium (Tl) is considered hazardous to health because of its high toxicity and is an emerging contaminant with two oxidation states: Tl (I) and Tl (III). However, the toxicity of Tl and its compounds can be influenced by the oxidation state of the metal. Tl (III) is the least studied oxidation state of Tl, although it may affect cell proliferation and has genotoxic potential. Therefore, the aim of the present study was to analyze the effects Tl (III) chloride (TlCl3) on cell cycle progression, the induction of DNA damage, and oxidative stress in human lymphocytes in vitro. There were no changes in cell viability after treatment with different concentrations (0.1, 0.5, 1, 5, 10, and 50 μg/mL) of TlCl3 for different exposure durations (1, 3, and 24 h), and a reduction in the number of viable cells was observed only after treatment with high concentrations (10 and 50 μg/mL) for 72 h. In addition, cells treated with 5–50 μg/mL TlCl3 for 48 and 72 h arrested in G1 phase. Moreover, TlCl3 increased DNA damage by activating the enzyme formamidopyrimidine DNA-glycosylase (FPG), which oxidized DNA bases and increased the production of reactive oxygen species. In conclusion, TlCl3 induces oxidative stress and DNA damage by oxidizing DNA bases, which may disrupt the cell cycle.